(untitled) (REVISTA NODO, 2021)
This paper approaches the notion of creation and its cognitive value in the production of sensitive knowledge, and its ability to transform human beings and symbolic universes they invent. Creation is an exercise of intersection, of interaction and dialogue between individuals, their knowledge and life, through which humans serve as producers and makers of open, community of knowledge. Aesthetics should be approached to understand sensitive knowledge, valuing its social and subjective adherence to the dynamics of intermnalization and externalization. It allows the unveilin of intersubjetive convergence space where artistic phenomena and issues of life are intertwined.